Seasonal Variation in Violent Victimization: Opportunity and the Annual Rhythm of the School Calendar - Carbone-López, Kristin Carmela (Journal of quantitative criminology, 2013)
Objectives This study draws on an underused source of data on seasonality—victim surveys—to assess whether violent crime occurs with greater frequency during summer months or whether it simply becomes known to police more often, and to examine the extent to which seasonal patterns in violent crime are differentiated based on victim characteristics and location of crime. Methods Data used come from the 1993–2008 National Crime Victimization Survey. Time series regression models are estimated to describe seasonal differences in violent crime victimization and reporting rates. Results Seasonal trends in youth violence stand in contrast to the trends for young and older adults, primarily due to their high risk of victimization at and near school. No evidence of seasonality is found in the extent to which serious violence becomes known to the police. However, simple assault is significantly more likely to come to the attention of the police during the summer months, primarily due to increases in the reporting of youth violence. Conclusions Our findings confirm some of the previous work on seasonal patterns in violent crime, but also show that these patterns vary across age groups, locations, and type of violence.